THE RESULTS OF DIAGNOSIS OF THE FORMATION OF STUDENTS’ PROFESSIONAL AND VALUE ORIENTATION TOWARDS LABOR ACTIVITY - Ohrimenko, Zorina (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article is devoted to the problem of formation of students’ professional and value orientations towards labor activity. The purpose of the article is to highlight the results of the diagnosis of professional and value orientations towards labor activity among adolescents and high school students (who receive educational services in general secondary education) and determine the levels of their formation. Using a set of diagnostic techniques, each of which is aimed at studying a specific indicator, and together they allowed to make a generalization about the peculiarities of the process of modern students’ professional self-determination, which is characterized by the appropriation of certain values and their awareness educational and professional activities. It is emphasized that the content of all covered methods has a clearly defined purpose, procedure, instructions, criteria, levels and description of results. The concrete results of empirical study of levels of students’ development of professional and value orientations towards labor activity on each component (cognitive, emotionally-motivational, arbitrary impulse, practically effective, self-valuable) are resulted and interpreted. The levels of formation of students’ development of professional and value orientations towards labor activity are empirically determined: high, medium, low. The analysis of psychological and pedagogical achievements on relevant research topics made it possible to make a generalization about the relevance and identity of the results of the study of the formation of students’ development of professional and value orientations towards labor activity. The conclusions emphasize that the vast majority of students have professional self-determination is difficult, because the ability of an individual to choose a profession is associated with the ability to make decisions, awareness of professional goals and ways to achieve it through professional self-determination, so choosing a profession is a voluntary act associated with a sense of self-worth and self-efficacy. Accordingly, the formation students’ development of professional and value orientations towards labor activity requires purposeful support of the student in the educational environment. The practical significance of the article is that its materials can be used in the process of vocational guidance for adolescents and high school students for professional diagnosis and professional information.